Production of defensive metabolites by Pinus patula X Pinus tecunumanii hybrids in response to Fusarium circinatum infection - Hammerbacher, Almuth (University of Pretoria, 2022)
Dissertation (MSc (Microbiology))--University of Pretoria, 2022.